Invasive extramammary Paget’s disease of the vulva: a multimodality organ‑preserving approach - Babu, Mohan; Natasha, Laishram; Devi, Laishram Purnima; Devi, Akoijam Sunita; Sharma, Prana; Saha, Pritam (International Journal of Research in Medical Sciences, 2026)
Extramammary Paget’s disease (EMPD) of the vulva is an uncommon intraepidermal adenocarcinoma of apocrine gland- bearing skin, typically affecting elderly women. It frequently presents as a chronic pruritic eczematous lesion and is often misdiagnosed as benign dermatoses, leading to delay in diagnosis. While many cases remain intraepidermal, a subset progresses to invasive disease with stromal and visceral involvement, associated with nodal and distant metastasis and worse prognosis. There is no universally accepted standard for locally advanced invasive EMPD; surgery, radiotherapy, and systemic therapy are all used in various combinations. A 70‑year‑old postmenopausal woman presented with invasive vulvar EMPD with bladder base infiltration, staged as T2N1M0 (stage IIIA). She received neoadjuvant paclitaxel- carboplatin chemotherapy followed by definitive external beam radiotherapy to the pelvis with a vulvar boost after declining radical vulvectomy. She achieved a partial response to chemotherapy and remains disease‑free on follow‑up after completion of radiotherapy, illustrating the role of individualized multimodal, organ‑preserving treatment in invasive vulvar EMPD.